Étude de la récidive post-traitement chez des agresseurs sexuels judiciarisés - Pellerin, Bruno; Proulx, Jean; Ouimet, Marc; Paradis, Yves; McKibben, André; Aubut, Jocelyn (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1996)
The aim of the current study was to assess the role of a treatment program (uncompleted; completed ; extended) on the posttreat-ment recidivism of sexual aggressors. Data on five types of recidivism (sexual ; violent ; property offense ; against a person ; total) were gathered for 102 pedophiles and 70 rapists. The recidivism rates for pedophiles who completed the treatment program was lower than for those of the pedophiles who did not complete the treatment. As to the rapists, the recidivism rates were lower for those who underwent an extended treatment program than for the other two groups. These data show that a treatment program reduces the recidivism rate in sexual aggressors. The optimal duration of treatment, however, varies according to the type of offender.